In < 3 + > and F <-> co-doped TiO2 giant dielectric ceramic material and preparation method thereof
By co-doping TiO2 giant dielectric ceramic materials in In3+ and F-, the shortcomings in dielectric properties and stability of the existing TiO2-based materials are solved, and the effects of high dielectric constant, low dielectric loss and good stability are achieved.
Patent Information
- Application Number
- CN202411747275.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-02
- Publication Date
- 2025-03-14
AI Technical Summary
The existing TiO2-based giant dielectric ceramic materials are difficult to maintain good frequency and temperature stability while increasing the dielectric constant and reducing dielectric loss, and the traditional donor doping strategy provides electrons has limitations.
In3+ and F-co-doped TiO2 giant dielectric ceramic material, the Ti position and O position are simultaneously doped in the TiO2 system through the InF3 raw material. In3+ generates oxygen vacancies, and F-substitutes O position to provide electrons, adjusts the oxygen vacancies concentration, and improves semiconductors.
High dielectric constants (up to 33429) and low dielectric losses (down to 0.06), as well as good frequency and temperature stability (meets X9R standards), while simplifying the preparation process and reducing costs.
Smart Images

Figure CN119613102A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of ceramic materials, and relates to giant dielectric ceramic materials and preparation methods thereof, and specifically to an In 3+ and F - Co-doped TiO2 giant dielectric ceramic material and preparation method. Background Art
[0002] In recent years, TiO2-based giant dielectric ceramics have become one of the research hotspots as a new type of multilayer ceramic capacitor (MLCC) dielectric material and a candidate material for the development and design of a new generation of high-end weapons and equipment and integrated circuits. Reference 1 (WB Hu et al, Nature Mater., 12 (2013) 821.) first reported the 5+ ), acceptor (In 3+ ) co-doped TiO2 ceramics to obtain high dielectric constants (greater than 10 4 ), low dielectric loss (less than 0.05) and good frequency and temperature stability. In recent years, researchers have focused on obtaining giant dielectric properties of TiO2-based materials through the co-doping strategy of donor and acceptor ions. For example, different donor doping (V 5+ , Nb 5+ and Ta 5+ ) and the recipient (In 3+ ) co-doped TiO2 ceramics; Reference 3 (XBZhou et al, Ceram.Int., 46 (2020) 11921-11925.), Reference 4 (J.Liu et al, Ceram.Int., 46 (2020) 12059-12066.) and Reference 5 (BCGuo et al, Ferroelectrics., 589 (2022) 35-44.) reported different acceptor ion doping (such as: Ag + , Ca 2+ , Sr 2+ , Ba 2+ 、Nd 3+ 、Sm 3+ ,La 3+ and Gd 3+ ) and donor (Nb 5+ and Ta 5+) co-doped TiO2 ceramics have obtained giant dielectric properties. Among them, the donor ion doping replaces the Ti site to produce electrons, and the acceptor ion doping generates oxygen vacancies. The researchers attributed the giant dielectric mechanism mainly to the effects of electron pinning defect dipole (EPDD), internal barrier layer capacitance (IBLC) and surface barrier layer capacitance (SBLC). Among them, the electrons provided by the donor dopant are in the triangle or diamond The oxygen vacancies caused by host ion doping are the key to the formation of defect dipole clusters. In the IBLC polarization mechanism, electron hopping polarization such as Ti 4+ +e→Ti 3+ It will cause the semiconducting characteristics of the grains, thereby obtaining a high dielectric constant. In the two dominant dielectric mechanisms (EPDD and IBLC), oxygen vacancies form defect dipole clusters in the former, while in the latter, it is believed that interface polarization is formed at the grain boundary, and electrons exist in the form of localized or long-range hopping conduction. When a large number of oxygen vacancies are generated, it will lead to the disassociation of defect clusters and conduction losses, which will inevitably increase dielectric losses. Therefore, it is very important to develop a new type of ion doping to reduce the oxygen vacancy concentration of TiO2 materials and break the traditional donor doping strategy of providing electrons to improve the dielectric properties of the current traditional donor and acceptor co-doped TiO2 giant dielectric materials. Summary of the invention
[0003] In view of the shortcomings of the prior art, the present invention aims to provide an In-type dielectric having high dielectric constant, low dielectric loss, good frequency and temperature stability. 3+ and F - The co-doped TiO2 giant dielectric ceramic material and preparation method have single raw materials, simple preparation process, good repeatability and low cost.
[0004] In order to achieve the above object, the present invention adopts the following technical solutions:
[0005] A kind of 3+ and F - Co-doped TiO2 giant dielectric ceramic material, the general structural formula is In x Ti 1-3x / 2 O 2-3x F 3x , where the value of x is 0.03~0.06.
[0006] Preferably, the general structural formula is In x Ti 1-3x / 2 O 2-3x F 3x , where x=0.05.
[0007] The present invention is to protect a kind of In as described above 3+and F - The preparation method of the co-doped TiO2 giant dielectric ceramic material comprises the following steps:
[0008] Step 1: According to the stoichiometric ratio, weigh InF3 and TiO2 powder raw materials respectively, put the weighed raw materials into a ball mill, ball mill, dry, grind and sieve to obtain a raw material mixture;
[0009] Step 2, placing the raw material mixture into an alumina crucible, placing the crucible in a box furnace, heating from room temperature to 1050-1250° C. in an air atmosphere, pre-firing for 1-4 hours, ball milling, drying, grinding and sieving to obtain pre-firing powder;
[0010] Step 3: Press the pre-sintered powder into tablets and place them in a tubular furnace. In a nitrogen atmosphere, heat the mixture from room temperature to 1220-1400°C and keep the temperature for 3-8 hours. Finally, cool the mixture naturally to room temperature to obtain a ceramic material with high dielectric constant, low dielectric loss and good temperature stability.
[0011] Preferably, the ball milling in step 1 and step 2 is performed using zirconium oxide balls as grinding balls and deionized water as ball milling medium, and the mixture is fully mixed and ball milled for 6 to 8 hours.
[0012] Preferably, the drying in step 1 and step 2 is performed by placing the product in an oven at 80-100° C. for 24 hours.
[0013] Preferably, the grinding in step 2 is further grinding in a mortar for 30 to 60 minutes.
[0014] Preferably, the sieving in step 2 is through a 120-200 mesh sieve.
[0015] Preferably, the pre-sintered powder tablets described in step 3 are pre-pressed into cylindrical green bodies with a diameter of 8 mm using a grinding tool, and then cold isostatically pressed for 3 to 5 minutes at a pressure of 200 MPa in a cold isostatic press.
[0016] Compared with the prior art, the present invention has the following technical effects:
[0017] The present invention breaks the traditional strategy of co-doping the TiO2 system with donor and acceptor ions, and only uses one raw material, InF3, to achieve simultaneous doping substitution at the Ti and O positions of the TiO2 system. 3+ As an acceptor doping to generate oxygen vacancies; F - Substitute O to provide electrons, and F with high electronegativity - Localized electrons are beneficial to Ti 4+ +e→Ti 3+ , improve the semiconductivity, and at the same time adjust the oxygen vacancy concentration; the prepared In 3+ and F -Co-doped TiO2 giant dielectric ceramic materials have high dielectric constant, low dielectric loss, good frequency and temperature stability. 0.05 Ti 0.925 O 1.85 F 0.15 Giant dielectric ceramics have a dielectric constant as high as 33429, a loss as low as 0.06, and a temperature stability of X9R;
[0018] The invention has single raw material, simple preparation process, good repeatability, low cost and high yield. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 In prepared in Examples 1 to 4 3+ and F - XRD patterns of co-doped TiO2 giant dielectric ceramic materials;
[0020] Figure 2 In prepared in Examples 1 to 4 3+ and F - The curves of dielectric constant and dielectric loss of co-doped TiO2 giant dielectric ceramic materials changing with frequency at 1kHz room temperature;
[0021] Figure 3 It is the temperature stability spectrum of the InF3-doped TiO2 giant dielectric ceramic material prepared in Examples 1 to 4 at 1 kHz. DETAILED DESCRIPTION
[0022] The specific contents of the present invention are further explained in detail below in conjunction with embodiments.
[0023] Example 1
[0024] Step 1: Follow In 0.05 Ti 0.925 O 1.85 F 0.15 2.0836 g of InF3 with a purity of 99.99% and 17.9184 g of TiO2 with a purity of 99.99% were weighed respectively, put into a nylon jar, and milled for 6 hours in a ball mill at a speed of 400 rpm using zirconium balls as grinding balls and deionized water as ball milling media, dried at 80°C for 24 hours, ground in a mortar for 30 minutes, and passed through a 120-mesh sieve to obtain a raw material mixture;
[0025] Step 2: placing the raw material mixture in an alumina crucible, compacting it with an agate rod, covering it, and then placing the crucible in a box furnace, heating it from room temperature to 1150°C at a heating rate of 5°C / min in an air atmosphere, keeping it warm for 2 hours, cooling it naturally to room temperature with the furnace, taking it out of the furnace, ball milling it with a ball mill at a speed of 400 rpm for 6 hours, placing it in a drying oven at 80°C for 24 hours, grinding it with a mortar for another 30 minutes, and passing it through a 120-mesh sieve to obtain a pre-calcined powder;
[0026] Step 3: Place the pre-sintered powder into a stainless steel mold with a diameter of 8 mm, press it into a cylindrical body without pressure using a powder tablet press, place the cylindrical body in a cold isostatic press, and cold isostatic press for 3 minutes at a pressure of 200 MPa; place the cylindrical body on a zirconia zirconium plate, place the zirconia zirconium plate in a tubular furnace, introduce a nitrogen atmosphere and heat it to 1370°C at a heating rate of 5°C / min / min, keep it warm for 4 hours, and cool it naturally to room temperature with the furnace to obtain In 3+ and F - Co-doped TiO2 giant dielectric ceramic materials.
[0027] Example 2
[0028] Step 1: Follow In 0.03 Ti 0.955 O 1.91 F 0.09 1.2662 g of InF3 with a purity of 99.99% and 18.7359 g of TiO2 with a purity of 99.99% were weighed respectively, put into a nylon jar, and milled for 7 hours in a ball mill at a speed of 400 rpm using zirconium balls as grinding balls and deionized water as ball milling media, dried at 90°C for 24 hours, ground in a mortar for 50 minutes, and passed through a 150-mesh sieve to obtain a raw material mixture;
[0029] Step 2: placing the raw material mixture in an alumina crucible, compacting it with an agate rod, covering it, and then placing the crucible in a box furnace, heating it from room temperature to 1050°C at a heating rate of 5°C / min in an air atmosphere, keeping it warm for 4 hours, cooling it naturally to room temperature with the furnace, taking it out of the furnace, ball milling it with a ball mill at a speed of 400 rpm for 7 hours, placing it in a drying oven at 90°C for 24 hours, grinding it with a mortar for another 50 minutes, and passing it through a 150-mesh sieve to obtain a pre-calcined powder;
[0030] Step 3: Place the pre-sintered powder into a stainless steel mold with a diameter of 8 mm, press it into a cylindrical body without pressure using a powder tablet press, place the cylindrical body in a cold isostatic press, and cold isostatic press for 4 minutes at a pressure of 200 MPa; place the cylindrical body on a zirconia zirconium plate, place the zirconia zirconium plate in a tubular furnace, introduce a nitrogen atmosphere and heat it to 1220°C at a heating rate of 5°C / min / min, keep it warm for 8 hours, and cool it naturally to room temperature with the furnace to obtain In3+ and F - Co-doped TiO2 giant dielectric ceramic materials.
[0031] Example 3
[0032] Step 1: Follow In 0.04 Ti 0.94 O 1.88 F 0.12 1.6775 g of InF3 with a purity of 99.99% and 18.3241 g of TiO2 with a purity of 99.99% were weighed respectively, put into a nylon jar, and milled for 8 hours in a ball mill with zirconium balls as grinding balls and deionized water as ball milling media at a speed of 400 rpm, dried at 100°C for 24 hours, ground in a mortar for 60 minutes and passed through a 200-mesh sieve to obtain a raw material mixture;
[0033] Step 2: placing the raw material mixture in an alumina crucible, compacting it with an agate rod, covering it, and then placing the crucible in a box furnace, heating it from room temperature to 1250°C at a heating rate of 5°C / min in an air atmosphere, keeping it warm for 1 hour, cooling it naturally to room temperature with the furnace, taking it out of the furnace, ball milling it with a ball mill at a speed of 400 rpm for 8 hours, placing it in a drying oven at 100°C for 24 hours, grinding it with a mortar for another 60 minutes, and passing it through a 200-mesh sieve to obtain a pre-calcined powder;
[0034] Step 3: Place the pre-sintered powder into a stainless steel mold with a diameter of 8 mm, press it into a cylindrical body without pressure using a powder tablet press, place the cylindrical body in a cold isostatic press, and cold isostatic press for 5 minutes at a pressure of 200 MPa; place the cylindrical body on a zirconia zirconium plate, place the zirconia zirconium plate in a tubular furnace, introduce a nitrogen atmosphere, and heat it to 1400°C at a heating rate of 5°C / min / min, keep it warm for 3 hours, and cool it naturally to room temperature with the furnace to obtain In 3+ and F - Co-doped TiO2 giant dielectric ceramic materials.
[0035] Example 4
[0036] Step 1: Follow In 0.06 Ti 0.91 O 1.82 F 0.18 2.4847 g of InF3 with a purity of 99.99% and 17.5175 g of TiO2 with a purity of 99.99% were weighed respectively, put into a nylon jar, and milled for 6 hours in a ball mill at a speed of 400 rpm using zirconium balls as grinding balls and deionized water as ball milling media, dried at 80°C for 24 hours, ground in a mortar for 30 minutes, and passed through a 120-mesh sieve to obtain a raw material mixture;
[0037] Step 2: placing the raw material mixture in an alumina crucible, compacting it with an agate rod, covering it, and then placing the crucible in a box furnace, heating it from room temperature to 1150°C at a heating rate of 5°C / min in an air atmosphere, keeping it warm for 2 hours, cooling it naturally to room temperature with the furnace, taking it out of the furnace, ball milling it with a ball mill at a speed of 400 rpm for 6 hours, placing it in a drying oven at 80°C for 24 hours, grinding it with a mortar for another 30 minutes, and passing it through a 120-mesh sieve to obtain a pre-calcined powder;
[0038] Step 3: Place the pre-sintered powder into a stainless steel mold with a diameter of 8 mm, press it into a cylindrical body without pressure using a powder tablet press, place the cylindrical body in a cold isostatic press, and cold isostatic press for 3 minutes at a pressure of 200 MPa; place the cylindrical body on a zirconia zirconium plate, place the zirconia zirconium plate in a tubular furnace, introduce a nitrogen atmosphere and heat it to 1370°C at a heating rate of 5°C / min / min, keep it warm for 4 hours, and cool it naturally to room temperature with the furnace to obtain In 3+ and F - Co-doped TiO2 giant dielectric ceramic materials.
[0039] Figure 1 In prepared in Example 1-4 3+ and F - From the XRD patterns of the co-doped TiO2 giant dielectric ceramic materials, it can be seen that the samples all obtained a pure rutile TiO2 phase structure without a second phase, and all doping elements entered the TiO2 lattice, indicating that Examples 1-4 prepared pure rutile TiO2 ceramic samples.
[0040] Figure 2 In prepared in Example 1-4 3+ and F - The curves of dielectric constant and dielectric loss of co-doped TiO2 giant dielectric ceramic materials changing with frequency at 1kHz room temperature are shown in the figure. Figure 2 All samples can obtain giant dielectric properties. When x = 0.05, the dielectric constant is as high as 33429 and the loss is only 0.06.
[0041] Figure 3 The temperature stability of the InF3-doped TiO2 giant dielectric ceramic material prepared in Example 1-4 at 1kHz. When x = 0.05, X9D (Δε r / ε 25 ℃: -55℃-200℃≤±15%). When x=0.04 and 0.06, Y8D(Δε r / ε 25 ℃: -30℃-150℃≤±15%) temperature stability.
[0042] It should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it; without departing from the concept of the present invention, the deduction or replacement made by those skilled in the art shall fall within the protection scope of the present invention.
Claims
1. An In 3+ and F - Co-doped TiO2 giant dielectric ceramic material, characterized in that: The general structural formula is In x Ti 1-3x / 2 O 2- 3x F 3x , where the value of x is 0.03~0.
06.
2. The In as claimed in claim 1 3+ and F - Co-doped TiO2 giant dielectric ceramic material, characterized in that: The general structural formula is In x Ti 1-3x / 2 O 2-3x F 3x , where x=0.
05.
3. An In as claimed in claim 1 or 2 3+ and F - The method for preparing a co-doped TiO2 giant dielectric ceramic material is characterized in that: The following steps are involved: Step 1: According to the stoichiometric ratio, weigh InF3 and TiO2 powder raw materials respectively, put the weighed raw materials into a ball mill, ball mill, dry, grind and sieve to obtain a raw material mixture; Step 2, placing the raw material mixture into an alumina crucible, placing the crucible in a box furnace, heating from room temperature to 1050-1250° C. in an air atmosphere, pre-firing for 1-4 hours, ball milling, drying, grinding and sieving to obtain pre-firing powder; Step 3: Press the pre-sintered powder into tablets and place them in a tubular furnace. In a nitrogen atmosphere, heat the mixture from room temperature to 1220-1400°C and keep the temperature for 3-8 hours. Finally, cool the mixture naturally to room temperature to obtain a ceramic material with high dielectric constant, low dielectric loss and good temperature stability.
4. In as claimed in claim 3 3+ and F - The method for preparing a co-doped TiO2 giant dielectric ceramic material is characterized in that: The ball milling in step 1 and step 2 is performed by using zirconium oxide balls as grinding balls and deionized water as ball milling medium, and the mixture is fully mixed and ball milled for 6 to 8 hours.
5. In as claimed in claim 3 3+ and F - The method for preparing a co-doped TiO2 giant dielectric ceramic material is characterized in that: The drying in step 1 and step 2 is performed by placing the product in an oven at 80-100° C. for 24 hours.
6. In as claimed in claim 3 3+ and F - The method for preparing a co-doped TiO2 giant dielectric ceramic material is characterized in that: The grinding described in step 2 is grinding with a mortar for another 30 to 60 minutes.
7. The In as claimed in claim 3 3+ and F - The method for preparing a co-doped TiO2 giant dielectric ceramic material is characterized in that: The sieving described in step 2 is through a 120-200 mesh sieve.
8. In as claimed in claim 3 3+ and F - The method for preparing a co-doped TiO2 giant dielectric ceramic material is characterized in that: The pre-sintered powder tablets described in step 3 are pre-pressed into cylindrical green bodies with a diameter of 8 mm using a grinding tool, and then cold isostatically pressed for 3 to 5 minutes at a pressure of 200 MPa in a cold isostatic press.